3d-Printed body architecture - Leach, Neil; Farahi, Behnaz; Antonelli, Paola; Bitoni, Francis; Casas, Niccolo; Gannon, Madeline; Goldemberg, Eric; Koemer, Julia; Koolhaas, Rem D.; Louis-Rosenberg, Jesse; Ma, Steve (John Wiley & Sons, 2017)
"Some architects dream of 3D-printing houses. Some even fantasise about 3D-printing entire cities. But what is the real potential of 3D printing for architects? This issue focuses on another strand of 3D-printing practice emerging among architects operating at a much smaller scale that is potentially more significant. Several architects have been working with the fashion industry to produce some exquisitely designed 3D-printed wearables. Other architects have been 3D-printing food, jewellery and other items at the scale of the human body. But what is the significance of this work? And how do these 3D-printed body-scale items relate to the discipline of architecture? Are they merely a distraction from the real business of the architect? Or do they point towards a new form of proto-architecture – like furniture, espresso makers and pavilions before them – that tests out architectural ideas and explores tectonic properties at a smaller scale? Or does this work constitute an entirely new arena of design? In other words, is 3D printing at the human scale to be seen as a new genre of 'body architecture'? This issue contains some of the most exciting work in this field today, and seeks to chart and analyse its significance."--